Smart Service Methods and Systems Based on Innovation and Entrepreneurship Platforms - Junhua, Rao (2024 IEEE International Conference on Information Technology, Electronics and Intelligent Communication Systems (ICITEICS), 2024)
In today's rapid development of high technology, the use of scientific and technological means to make the development of innovation and entrepreneurship platform better has made a trend, in order to more adapt to the current development, create a smart innovation and entrepreneurship platform, so that the efficiency of the innovation and entrepreneurship platform is improved, and the innovation and entrepreneurship platform follows. In the innovation and entrepreneurship platform, it is very important to collect, analyze and process the information of the living organisms in the innovation and entrepreneurship platform, so as to achieve the efficient realization of the innovation and entrepreneurship platform. Iterative algorithms cannot accurately collect and analyze information problems in innovation and entrepreneurship platforms. Therefore, this paper proposes a data fusion algorithm for intelligent service methods and system analysis. First, computer technology is used to collect Internet information, and indicators is divided according to smart service methods and system requirements to reduce interference factors in smart service methods and systems. Then, computer technology forms the smart service method and system scheme of the innovation and entrepreneurship platform smart service method and system results, and comprehensively analyzes the smart service method and system results. MATLAB simulation shows that under certain evaluation criteria, the data fusion algorithm is better than the iterative algorithm for the intelligent service method and system accuracy, smart service method and system reliability of the innovation and entrepreneurship platform.